1994
DOI: 10.1007/bf00757184
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adrenal cell functions by cadmium salts: 2. Sites affected by CdCl2 during unstimulated steroid synthesis

Abstract: In previous studies cadmium chloride (CdCl2) nonlethally inhibited Y-1 adrenal mouse adrenal tumour cell 20-dihydroxyprogesterone (20DHP) secretion, affecting unstimulated and stimulated steroidogenic pathway sites differently. We studied CdCl2 effects on unstimulated steroidogenesis using Y-1 cells incubated 0.5 h in medium with or without cadmium (using the concentration that inhibited ACTH-stimulated steroid secretion by 50%). Exogenously added 20-hydroxycholesterol (20OHC), 22(R)-hydroxycholesterol (22OHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As a result, data of Cd and ACTH and thyroid levels show that there are no relationships between each other. So that, when we focus on our data in the relation between ACTH and Cd, cannot cause an agreement on notice of relations of those parameters with the confirmation of Mgbonyebi et al [12][13]. The researchers mentioned that Cd toxicity in adrenal functions caused hyperactivity in ACTH stimulation and expression [12][13].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…As a result, data of Cd and ACTH and thyroid levels show that there are no relationships between each other. So that, when we focus on our data in the relation between ACTH and Cd, cannot cause an agreement on notice of relations of those parameters with the confirmation of Mgbonyebi et al [12][13]. The researchers mentioned that Cd toxicity in adrenal functions caused hyperactivity in ACTH stimulation and expression [12][13].…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, patients with end stage renal disease display a variety of endocrine disturbances [11]. Mgbonyebi et al [12][13], conclude that the toxicity of Cd in adrenal functions causes hyperactivity in ACTH stimulation and expression. Besides, disturbances in thyroid function are common among patients on renal replacement therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Adx shares some of the features of SpI, in what is nuclear encoded and located in the adrenal cortex mitochondria, where it transfers electrons to the mitochondrial cytochromes P-450, which act as steroid hydroxylases. However, cadmium is known to interfere with both adrenal steroid hydroxylation [44,451 and renal calcidiol hydroxylation [46], the latter depending on a system consisting of a reductase, a [2Fe-2S]-ferredoxin, and a cytochrome P-450. As cadmium is an antimetabolite to iron and is able to change the membrane permeability, and thus the utilization of steroids, differential inhibitionhnactivation mechanisms may play a role in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the adrenal gland, heavy metals are deposited in the lipid-rich cortex and block various enzymatic pathways, causing hyperandrogenemia or partial hypoandrenalism. 88,89 Klages et al 90 reported that hypo- and hyperthyroidism could result from Pb and Cd exposure. These hormonal changes might be possible in human also due to environmental exposure to various environmental persistent chemicals including heavy metals and pesticides.…”
Section: Solvent Exposurementioning
confidence: 99%